Safety and High Level Efficacy of the Combination Malaria Vaccine Regimen of RTS,S/AS01B With Chimpanzee Adenovirus 63 and Modified Vaccinia Ankara Vectored Vaccines Expressing ME-TRAP - Rampling, T; Ewer, KJ; Bowyer, G; Bliss, CM; Edwards, NJ; Wright, D; Payne, RO; Venkatraman, N; de Barra, E; Snudden, CM; Poulton, ID; de Graaf, H; et al. (Oxford University Press, 2016)
The need for a highly efficacious vaccine against Plasmodium falciparum remains pressing. In this controlled human malaria infection (CHMI) study, we assessed the safety, efficacy and immunogenicity of a schedule combining 2 distinct vaccine types in a staggered immunization regimen: one inducing high-titer antibodies to circumsporozoite protein (RTS,S/AS01B) and the other inducing potent T-cell responses to thrombospondin-related adhesion protein (TRAP) by using a viral vector.Thirty-seven healthy malaria-naive adults were vaccinated with either a chimpanzee adenovirus 63 and modified vaccinia virus Ankara-vectored vaccine expressing a multiepitope string fused to TRAP and 3 doses of RTS,S/AS01B (group 1; n = 20) or 3 doses of RTS,S/AS01B alone (group 2; n = 17). CHMI was delivered by mosquito bites to 33 vaccinated subjects at week 12 after the first vaccination and to 6 unvaccinated controls.No suspected unexpected serious adverse reactions or severe adverse events related to vaccination were reported. Protective vaccine efficacy was observed in 14 of 17 subjects (82.4%) in group 1 and 12 of 16 subjects (75%) in group 2. All control subjects received a diagnosis of blood-stage malaria parasite infection. Both vaccination regimens were immunogenic. Fourteen protected subjects underwent repeat CHMI 6 months after initial CHMI; 7 of 8 (87.5%) in group 1 and 5 of 6 (83.3%) in group 2 remained protected.The high level of sterile efficacy observed in this trial is encouraging for further evaluation of combination approaches using these vaccine types.NCT01883609.